2012
DOI: 10.1530/eje-12-0214
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of GH treatment on coagulation, fibrinolysis, inflammation biomarkers, and insulin resistance status in prepubertal children with GH deficiency

Abstract: At early ages, GH therapy appears to exert beneficial effects on the amount of aPAI-1. At the same time, it increases the state of insulin resistance (HOMA-IR index) without modifying the levels of fibrinogen, vWF, CRP, and IL6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
(34 reference statements)
3
18
0
6
Order By: Relevance
“…Other studies have reported even increased insulin sensitivity in young pre- or early pubertal children, and that there is progressive deterioration in this insulin sensitivity with advancing age and pubertal development. [2930]…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported even increased insulin sensitivity in young pre- or early pubertal children, and that there is progressive deterioration in this insulin sensitivity with advancing age and pubertal development. [2930]…”
Section: Discussionmentioning
confidence: 99%
“…Data derived from a cohort of 36 prepubertal children with GHD showed higher levels of fibrinogen and activated PAI‐1 compared with controls. Reduction in PAI‐1 concentrations, but not in fibrinogen and vWF levels, was observed after 6 months of GH replacement therapy …”
Section: Pituitary Disordersmentioning
confidence: 95%
“…A number of serum circulating markers, including C-reactive protein (CRP), fibrinogen, active plasminogen activator inhibitor type-1 and homocysteine have been proposed as potential risk factors for atherothrombotic vascular disease [17,18]. …”
Section: Biochemical Alterations and The Effect Of R-hgh Therapymentioning
confidence: 99%
“…In the pediatric population, a few studies have been reported, some in adolescents with GHD, finding elevated CRP and fibrinogen levels [16,22,23,24]; however, less studies were conducted in prepubertal children with the identification of high levels of fibrinogen, CRP and homocysteine [11,16,17,25]. Of note, in all these studies, the biochemical parameters were reversed by short-term r-hGH therapy.…”
Section: Biochemical Alterations and The Effect Of R-hgh Therapymentioning
confidence: 99%